PENERAPAN METODE TALKING STICK YANG DILENGKAPI DENGAN REINFORCEMENT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR ILMU PENDIDIKAN SOSIAL SISWA - Anis Wahyuningsih (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This research was conducted at Seririt State Vocational School 1 in Class XII 4 Hospitality Accommodation where the students' ability to study social studies was quite low. The purpose of writing this class action research is to find out whether the talking stick method which is equipped with reinforcement can improve student learning achievement. The data collection method is a learning achievement test. The data analysis method is descriptive. The results obtained from this study are the talking stick method that is equipped with reinforcement can improve student motivation and learning outcomes. This is evident from the average results obtained initially 71.44 in the first cycle to 77.66 and in the second cycle to 85.17. The conclusion obtained from this study is the talking stick method that is equipped with reinforcement can improve the learning achievement of social studies class XII Hospitality Accommodation 4 Vocational High School 1 Seririt.